2017
DOI: 10.1097/gox.0000000000001495
|View full text |Cite
|
Sign up to set email alerts
|

Scar Tissue Causing Saphenous Nerve Entrapment: Percutaneous Scar Release and Fat Grafting

Abstract: Summary:Painful neuropathies can be caused by nerve compression or neuromas. Nerve compressions can arise from scar adhesions causing painful posttraumatic entrapment of nerve branches via fibrosis. The classical treatment methods include neurolysis and nerve transposition. In this case, we present the treatment of recurrent scar entrapment of the saphenous nerve with percutaneous neurolysis and lipofilling in a patient who had previously undergone an open neurolysis procedure. Resolution of the condition with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Although the use of this technique has already been reported in the buttock [11] and lower extremities [12], to the best of our knowledge, no study has evaluated its safety and effectiveness in breast surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of this technique has already been reported in the buttock [11] and lower extremities [12], to the best of our knowledge, no study has evaluated its safety and effectiveness in breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on a new fat processing technique that involves adipose tissue washing, "micronization," and decantation. This technique has been reported in a few studies in the scientific literature [11,12], but, to the best of our knowledge, no study on its safety and effectiveness in a sufficiently large patient series has been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Non-surgical causes of IBSN injury are less prevalent. Macrotrauma from a fall [6,18] or a direct blow to the medial thigh or knee [6,15,21,22] have been reported. Additionally, overuse injuries from running [12,17,20] have been suspected of causing damage to the IBSN.…”
Section: Etiologymentioning
confidence: 99%
“…Some authors contest the reliability of these methods [2,13,14,24], and it has been suggested that missed diagnoses may be consequent to focus on the primary branch of the saphenous nerve and not the infrapatellar branch [10]. Imaging, via magnetic resonance imaging (MRI) or computerized tomography (CT), is also utilized for diagnosis [18,22,24,25,61,62]. Occasionally, exploratory surgery is required to identify injury to the IBSN [1,13].…”
Section: Examination Relevant Findingsmentioning
confidence: 99%
See 1 more Smart Citation